VOICETHREAD UTILIZATION AS SPEAKING SKILL ENHANCEMENT FOR STUDENTS IN EFL CONTEXT - Qurrotu Inayatil Maula (Widyagogik, 2022)
This study is aimed at enhancing students’ speaking skills utilizing VoiceThread (VT) in EFL context since most of the students perceived that they got difficulties in speaking skills. Despite the difficulties in speaking, they perceived that mastering English speaking skills was essential to support their academic and career in the future. Due to the limitation in learning English in class causing limited time to develop speaking skills, VT is proposed as an additional instructional learning platform to support students’ learning outside the class. Using Classroom Action Research (CAR), this study was carried out following the steps of CAR proposed by Kemmis and McTaggart, i.e. planning, acting, observing, and reflecting. The research subjects were 34 students of Elementary School Teacher Education Study Program who were taking English course as one of the compulsory courses in the university. In utilizing VT, some procedures were carried out: 1) introducing VT, 2) introducing vocabulary and grammar used in the materials, 3) listening to an example how to do the task, 4) giving comments, and 5) getting feedback. At the end, after utilizing VT, it is found that VT can help students enhance their ability in speaking English.